2018
DOI: 10.30737/ekonika.v3i1.105
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Pengembangan Pemasaran Digital Pada Startup’s (Studi Kasus Pada Wirausaha Baru)

Abstract: This study aims to reveal the impact of digital marketing management on start -up. The study is a case study in an effort to show how the actual impact of digital marketing on start-ups. This research is a qualitative research with etnometodology approach. The study was conducted by direct observation and in-depth interviews on the new entrepreneurial community that became the vendor in the start-up of e-commerce at the Faculty of Economics, University of Nusantara PGRI Kediri. Informants selected with criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
0
4
0
6
Order By: Relevance
“…Banyak penelitian yang membuktikan hal tersebut. Contohnya penelitian yang dilakukan oleh (Aliami et al, 2018) memperlihatkan bahwa pengelolaan digital marketing memberikan dampak terhadap peningkatan bisnis start-up. Melalui penerapan digital marketing perusahaan dapat mempromosikan strategi keberlanjutan mereka dan memberi informasi kepada pengguna tentang promosi atau aktivitas keberlanjutan mereka (Saura et al, 2020).…”
Section: Pendahuluanunclassified
“…Banyak penelitian yang membuktikan hal tersebut. Contohnya penelitian yang dilakukan oleh (Aliami et al, 2018) memperlihatkan bahwa pengelolaan digital marketing memberikan dampak terhadap peningkatan bisnis start-up. Melalui penerapan digital marketing perusahaan dapat mempromosikan strategi keberlanjutan mereka dan memberi informasi kepada pengguna tentang promosi atau aktivitas keberlanjutan mereka (Saura et al, 2020).…”
Section: Pendahuluanunclassified
“…Furthermore, it is expected to be a reference for UMKMs on how to use an advantage strategy to compete with the Omnichannel Marketing digitalization system in order to survive in the midst of tight business competition as well as pandemic conditions that have hit the world. Research conducted (Aliami et al, 2018) revealed that digital marketing management has an impact on increasing start-up business revenue. However, what is often a problem is the lack of understanding of how to create good content.…”
Section: Introductionmentioning
confidence: 99%
“…This additionally affects the restricted tasks of MSMEs and less customers who shop straightforwardly contrasted with ordinary days. , buying and advertising items by using gadgets [1].…”
Section: Introductionmentioning
confidence: 99%